The economics of fraudulent accounting - Kedia, Simi; Philippon, Thomas (National Bureau of Economic Research, 2005)
"We argue that earnings management and fraudulent accounting have important economic consequences. In a model where the costs of earnings management are endogenous, we show that in equilibrium, bad managers hire and invest too much in order to pool with the good managers. This behavior distorts the allocation of economic resources among firms. We test the predictions of the model using new historical and firm-level data. First, we show that periods of high stock market valuations are systematically followed by large increases in reported frauds. We then show that during periods of suspicious accounting, firms hire and invest excessively, while insiders exercise options and sell stocks. When the misreporting is detected, firms shed labor and capital and productivity improves. In the aggregate, our model seems able to account for periods of jobless and investment-less growth"--National Bureau of Economic Research web site.
Keywords: Accounting fraud -- Economic aspects